2022
DOI: 10.3390/mi13030392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D Printing Technique and TPE Material on the Endurance of Pneumatic Linear Peristaltic Actuators

Abstract: In this paper, additive manufacturing was used in order to produce hose prototypes for peristaltic linear pneumatic actuators. In order to optimise the endurance of the actuator, we 3D printed different thermoplastic polyurethane elastomers with different shore hardness levels using ARBURG Plastic Freeforming technology. Furthermore, effects of the hose geometries on the lifetime of the actuator were investigated. Experimental evidence showed that the lifetime of the actuator was dependent on the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The research findings reported in the 3D-Printed Actuators Special Issue show promising approaches for engineering biology-like actuation. These findings have led to the following: the creation of an anatomically correct robotic hand with human-like grasping capabilities [ 1 ]; emulation of an antagonistic variable stiffness actuation observed in the musculoskeletal system of snakes [ 2 ]; reducing friction in rotating parts and joints by combining 3D printing and radiation pressure [ 3 ]; fabrication of flexible piezoelectric composite actuators without application of any adhesives [ 4 ]; extension of the service life of actuators through geometric and material optimization [ 5 ]; and acceleration of print inspection through an open-source low-power computer-vision hardware [ 6 ].…”
mentioning
confidence: 99%
“…The research findings reported in the 3D-Printed Actuators Special Issue show promising approaches for engineering biology-like actuation. These findings have led to the following: the creation of an anatomically correct robotic hand with human-like grasping capabilities [ 1 ]; emulation of an antagonistic variable stiffness actuation observed in the musculoskeletal system of snakes [ 2 ]; reducing friction in rotating parts and joints by combining 3D printing and radiation pressure [ 3 ]; fabrication of flexible piezoelectric composite actuators without application of any adhesives [ 4 ]; extension of the service life of actuators through geometric and material optimization [ 5 ]; and acceleration of print inspection through an open-source low-power computer-vision hardware [ 6 ].…”
mentioning
confidence: 99%